State of World Population 2000 - United Nations Population Fund (United Nations, 2000)
Despite the tremendous changes of the 20th century, discrimination and violence against women and girls remain firmly rooted in cultures around the world. This year’s Report looks at the gender inequality - the restrictions placed on women’s reproductive choices and how it affects their health, education, social and economic participation. The publication also explores women’s rights as human rights, gender violence and the role of men in reproductive health decisions. The Report acknowledges the role of governments in creating conditions for gender equality, but points out that in the end, different societies need their own solutions to provide a better life for both women and men. This annual also provides easily accessible tables and data representing trends and statistics for world population.